Repensar la enseñanza de la lengua española en la educación costarricense. Los alumnos en el proceso de transición sexto grado/ sétimo año. - Murillo Rojas, Marielos (2012)
The main aim of this article is to reflect about the transition between primary school and high school, it will be done in the context of the political education guides that appear in the “Ley Fundamental de Educación de Costa Rica”. Also, it suggest that the language as point articulated of school curriculum and the Spanish as a subject who will made the articulation. Therefore, it is necessary to reformulate the functions of Spanish teachers and it is important to increase the number of Spanish lessons.